2013
DOI: 10.1108/00242531311329473
|View full text |Cite
|
Sign up to set email alerts
|

A selective review of research on e‐resource usage in academic libraries

Abstract: PurposeThe purpose of this paper is to highlight the importance of quantitative and qualitative analysis of the usage of e‐resources in academic libraries. It also describes various studies undertaken to study the users' behavior and attitude towards e‐journals.Design/methodology/approachThe paper provides a comprehensive review of the recent published literature on the importance of the usage statistics of e‐resources subscribed to by the academic libraries.FindingsThe findings show that the usage statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 93 publications
(99 reference statements)
0
17
0
Order By: Relevance
“…Like Lamothe, this review confirmed that demographics of users are important and that increasing the volume of titles can be good for usage (Tripathi & Jeevan, 2013).…”
Section: What Does the Research Say?mentioning
confidence: 54%
“…Like Lamothe, this review confirmed that demographics of users are important and that increasing the volume of titles can be good for usage (Tripathi & Jeevan, 2013).…”
Section: What Does the Research Say?mentioning
confidence: 54%
“…Log analysis was first adapted for libraries by Nicholas, Huntington, and Watkinson (2005) as a means of dissecting user interactions with an electronic resource or platform. Since then, many other researchers have used log analysis to better understand e-resource usage patterns (Tripathi & Jeevan, 2013). The study at hand is similar in that it uses raw data to examine interactions with scholarly resources, but it also recalls web traffic analysis studies since web domain referrals are the primary focus.…”
Section: Commentarymentioning
confidence: 99%
“…Electronic databases were one of the major categories of electronic resources. Databases store rich information in a standard online platform, making it possible for libraries and information professionals to execute user studies and content reviews (Tripathi and Jeevan, 2013). Database usage statistics were, therefore, a common measurement of value used by libraries.…”
Section: Literature Reviewmentioning
confidence: 99%